2017
DOI: 10.1002/aoc.4019
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies, structural characterization and electrochemical studies of two cobalt (III) complexes with tridentate hydrazone Schiff base ligands: Evaluation of antibacterial activities, DNA‐binding, BSA interaction and molecular docking

Abstract: Co(III) complexes of tridentate Schiff base ligands derived from N‐(2‐hydroxybenzylideneamino)benzamide (H2L1) and 2‐(2‐hydroxybenzylidene)hydrazine‐1‐carboxamide (H2L2) were synthesized and characterized using IR, Raman, 1H–NMR and UV–Vis spectroscopies. X‐ray single crystal structures of complexes 1 and 2 have also been determined, and it was indicated that these Co(III) complexes are in a distorted octahedral geometry. The cyclic voltammetry (CV) of the complexes indicates an irreversible redox behavior for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The spectra of complex electron transitions relative to the ligands showed bands in the higher regions, which include absorption bands in the regions of 335, 349, 400, and 427 nm (for complex ( 1 )), 328, 346, 392, and 415 nm (for complex ( 2 )), and 336, 412, and 434 nm (for complex ( 3 )), which correspond to the intra‐ligand transitions of the azomethine group and the metal‐to‐ligand charge transfer (MLCT) transitions. [ 63‐65 ] These absorption bands at a high wavelength confirm the coordination of the cobalt(III) ion to the azomethine group (CN). Also, the wide shoulders observed in the 545, 614, and 668 nm regions are assigned to d → d transitions in cobalt complexes ( 1–3 ), respectively.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…The spectra of complex electron transitions relative to the ligands showed bands in the higher regions, which include absorption bands in the regions of 335, 349, 400, and 427 nm (for complex ( 1 )), 328, 346, 392, and 415 nm (for complex ( 2 )), and 336, 412, and 434 nm (for complex ( 3 )), which correspond to the intra‐ligand transitions of the azomethine group and the metal‐to‐ligand charge transfer (MLCT) transitions. [ 63‐65 ] These absorption bands at a high wavelength confirm the coordination of the cobalt(III) ion to the azomethine group (CN). Also, the wide shoulders observed in the 545, 614, and 668 nm regions are assigned to d → d transitions in cobalt complexes ( 1–3 ), respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Also, these results prove the coordination of the (O) 2‐hydroxy benzaldehyde ring of the ligand to the cobalt(III) ion. [ 63–65 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 As such, these complexes might be potentially useful for the treatment of cancer, 8,9 Alzheimer's disease, 10 inflammation, 11 or diseases caused by Gram-positive bacteria. 12 Previous studies have shown that the introduction of a methyl group onto the acylated nitrogen atom of acylhydrazones can lead to distinct biological responses. 3,[13][14][15] Although N-alkylation is of great interest, only limited range of N-alkyl derivatives of acylhydrazones are Scheme 1 N-Alkylation of 2-hydroxybenzaldehyde acylhydrazones known.…”
mentioning
confidence: 99%